Kecernaan Nutrien dan Status Fisiologis Domba Akhir Kebuntingan dengan Ransum Flushing Minyak Sawit dan Minyak Lemuru: Nutrient Digestibility and Physiological Status of Late Pregnancy Ewe fed with Flushing Diet Containing Palm Oil and Lemuru Oil - Lilis Khotijah; M Yasin; Didid Diapari; Dilla Mareistia Fassah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
The objective of this study was to evaluate nutrient digestibility and physiological status of local sheep at late pregnancy fed with flushing diet containing palm oil, lemuru oil, and their combination. In this research, the livestock used were 12 female local sheep at late pregnancy with an average body weight of 43.58 ± 5.57 kg were placed in metabolic cages. This study used a randomized block design (RBD) with 4 treatments and 3 block replications. The treatments were P1 = control ration (30% grass + 70% concentrate), P2 = control ration + 6% palm oil supplementation, P3 = control ration + 3% lemuru oil and 3% palm oil supplementation, P4 = control ration + 6% lemuru oil supplementation. The feed consumption, nutrient digestibility, and physiological status were measured in this study. The data obtained were analyzed using ANOVA. Means values differences were analyzed using Duncan test. The results showed that the addition of palm oil and lemuru oil to the concentrate diet increased (p<0.05) crude fat consumption, dry matter digestibility, and crude fat digestibility, but decreased (p<0.05) Nitrogen free extract consumption. Addition of palm oil and lemuru oil on the concentrate diet had no significant effect on dry matter consumption, crude protein consumption, crude fiber consumption, crude protein digestibility, crude fiber digestibility, Nitrogen free extract digestibility, and TDN value. The treatments did not affect significantly on physiological status. It can be concluded that the use of 6% palm oil in the ration can increase crude fat consumption and crude fat digestibility in pregnant ewes. Key words: digestibility, ewes, flushing, oil, physiological status